Solution-processed Li-doped ZnSnO metal-semiconductor-metal UV photodetectors. (16th June 2021) - Lin, Pei-Te; Huang, Wen-Chun; Lou, Yu-Qian; Yan, Cing-Yuan; Lin, Yu-Syuan; Chang, Chiao-Li; Chang, Po-Chih; Gong, Jyh-Rong; Hsueh, Wen-Jeng; Huang, Chun-Ying
Abstract: The electrical performance of thin-film transistors that use an amorphous oxide semiconductor (AOS) is significantly improved by incorporating metal cations as carrier suppressors. However, the effect of these elements on the performance of AOS-based photodetectors (PDs) is still unknown. This study uses a precursor containing lithium (Li) element and a sol-gel process to produce a Li-doped amorphous ZnSnO (a-ZTO) thin-film for UV PD applications. The results of x-ray photoelectron spectroscopy analysis show that the number of oxygen vacancies ( V o ) in a-ZTO thin-films decreases significantly from ∼32.1% to ∼14.4% after Li-doping (3 at%). The dark current decreases and the photocurrent increases in the ZTO-based PD so an ultra-high photo-to-dark current ratio (PDCR) of 1185 is achieved. The significant increase in PDCR means that solution-processed a-ZTO are eminently suited to use in UV PDs that use In-free AOSs.